2022
DOI: 10.1111/dth.15457
|View full text |Cite
|
Sign up to set email alerts
|

Comparative efficacy of using a combination of intralesional purified protein derivative with low dose isotretinoin in the treatment of recalcitrant common warts

Abstract: Intralesional immunotherapy with purified protein derivative (PPD) is an effective and tolerable therapeutic modality for the treatment of common warts. However, the complete clearance rates are still unsatisfactory. We thought to evaluate the efficacy and safety of adding low dose isotretinoin to intralesional PPD versus PPD monotherapy for viral warts. The study included two groups: Group (A) was treated by intralesional PPD at 2-week intervals until complete clearance or for a maximum of six sessions in add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…5 sessions 78.8 0 6 Erythema, pain, edema, low-grade fever Diab et al 4 2021 (Egypt) RCT PPD 20 Simple, recalcitrant; common 0.01 mL PPD-5TU, intralesion on largest wart 2-weeks interval, max. 6 sessions 35 0 6 Pain, myalgias, fever, erythema, edema, skin pigmentation Diab et al 28 2021 (Egypt) RCT PPD (A) PPD + iso-tretinoin (B) A: 20 B: 20 Simple, recalcitrant; common, plantar Group A: 0.1 mL PPD, intralesion on largest wart, 2-weeks interval, max. 6 sessions Group B: PPD as given in group A + low dose isotretinoin (0.2–0.4 mg/kg/day) for 3 months A: 35 B: 55 A: 0 B: 9.1 3 All groups: erythema, edema, pain, dis-pigmentation, fever, myalgias B: cheilitis, dry skin Durga-devi et al 29 2018 (India) Open label study PPD (1) Topical 5% 5-fluorouracil (2) 1: 25 2: 25 Simple, recalcitrant; peri-ungual, warts in other areas (not mentioned in detail) Group 1: PPD-1TU, volume injected determined by size of skin test reactivity according to Johnson et al 20 intralesion on one randomly selected lesion, 3-weeks interval, max.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…5 sessions 78.8 0 6 Erythema, pain, edema, low-grade fever Diab et al 4 2021 (Egypt) RCT PPD 20 Simple, recalcitrant; common 0.01 mL PPD-5TU, intralesion on largest wart 2-weeks interval, max. 6 sessions 35 0 6 Pain, myalgias, fever, erythema, edema, skin pigmentation Diab et al 28 2021 (Egypt) RCT PPD (A) PPD + iso-tretinoin (B) A: 20 B: 20 Simple, recalcitrant; common, plantar Group A: 0.1 mL PPD, intralesion on largest wart, 2-weeks interval, max. 6 sessions Group B: PPD as given in group A + low dose isotretinoin (0.2–0.4 mg/kg/day) for 3 months A: 35 B: 55 A: 0 B: 9.1 3 All groups: erythema, edema, pain, dis-pigmentation, fever, myalgias B: cheilitis, dry skin Durga-devi et al 29 2018 (India) Open label study PPD (1) Topical 5% 5-fluorouracil (2) 1: 25 2: 25 Simple, recalcitrant; peri-ungual, warts in other areas (not mentioned in detail) Group 1: PPD-1TU, volume injected determined by size of skin test reactivity according to Johnson et al 20 intralesion on one randomly selected lesion, 3-weeks interval, max.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, the low-dose isotretinoin did not add a therapeutic value for treating common warts. 28 …”
Section: Discussionmentioning
confidence: 99%
“… 143 Different results were found in a comparative study that showed no statistically significant difference between the combination of intralesional purified protein derivative (PPD) with a low dose isotretinoin and PPD alone regarding the therapeutic response. 144 …”
Section: Introductionmentioning
confidence: 99%